How do you evaluate e^( ( 11 pi)/6 i) - e^( ( 17 pi)/8 i)e11π6ie17π8i using trigonometric functions?

1 Answer

e^((11pi)/6i)-e^((17pi)/8i)=0.884e^(-1.505i)e11π6ie17π8i=0.884e1.505i

Explanation:

e^((11pi)/6i)-e^((17pi)/8i)=x+iye11π6ie17π8i=x+iy

e^((11pi)/6i)=cos((11pi)/6)+isin((11pi)/6)e11π6i=cos(11π6)+isin(11π6)

e^((17pi)/8i)=cos((17pi)/8)+isin((17pi)/8)e17π8i=cos(17π8)+isin(17π8)

e^((11pi)/6i)-e^((17pi)/8i)=(cos((11pi)/6)+isin((11pi)/6))-(cos((17pi)/8)+isin((17pi)/8))e11π6ie17π8i=(cos(11π6)+isin(11π6))(cos(17π8)+isin(17π8))

e^((11pi)/6i)-e^((17pi)/8i)e11π6ie17π8i
=(cos((11pi)/6)-cos((17pi)/8))=(cos(11π6)cos(17π8))
+i(sin((11pi)/6)-sin((17pi)/8))+i(sin(11π6)sin(17π8))

cos((11pi)/6)-cos((17pi)/8)=-2sin(((11pi)/6+(17pi)/8)/2)sin(((11pi)/6-(17pi)/8)/2)cos(11π6)cos(17π8)=2sin(11π6+17π82)sin(11π617π82)

(11pi)/6+(17pi)/8=(8xx11pi)/(8xx6)+(6xx17pi)/(6xx8)11π6+17π8=8×11π8×6+6×17π6×8

=(88pi)/48+(102pi)/48=((88+102)pi)/48=88π48+102π48=(88+102)π48

(11pi)/6+(17pi)/8=(190pi)/4811π6+17π8=190π48
(11pi)/6+(17pi)/8=(95pi)/2411π6+17π8=95π24

(11pi)/6-(17pi)/8=(8xx11pi)/(8xx6)-(6xx17pi)/(6xx8)11π617π8=8×11π8×66×17π6×8

=(88pi)/48-(102pi)/48=((88-102)pi)/48=88π48102π48=(88102)π48

(11pi)/6-(17pi)/8=(-14pi)/4811π617π8=14π48
(11pi)/6-(17pi)/8=(-7pi)/2411π617π8=7π24

1/2((11pi)/6+(17pi)/8)=(95pi)/4812(11π6+17π8)=95π48

1/2((11pi)/6-(17pi)/8)=(-7pi)/4812(11π617π8)=7π48

-2sin(((11pi)/6+(17pi)/8)/2)sin(((11pi)/6-(17pi)/8)/2)=-2sin((95pi)/48)sin((-7pi)/48)2sin(11π6+17π82)sin(11π617π82)=2sin(95π48)sin(7π48)

cos((11pi)/6)-cos((17pi)/8)=-2sin((95pi)/48)sin((-7pi)/48)cos(11π6)cos(17π8)=2sin(95π48)sin(7π48)

sin((11pi)/6)-sin((17pi)/8)=2cos(((11pi)/6+(17pi)/8)/2)sin(((11pi)/6-(17pi)/8)/2)sin(11π6)sin(17π8)=2cos(11π6+17π82)sin(11π617π82)

1/2((11pi)/6+(17pi)/8)=(95pi)/4812(11π6+17π8)=95π48

1/2((11pi)/6-(17pi)/8)=(-7pi)/4812(11π617π8)=7π48

sin((11pi)/6)-sin((17pi)/8)=2cos((95pi)/48)sin((-7pi)/48)sin(11π6)sin(17π8)=2cos(95π48)sin(7π48)

e^((11pi)/6i)-e^((17pi)/8i)e11π6ie17π8i
=(cos((11pi)/6)-cos((17pi)/8))=(cos(11π6)cos(17π8))
+i(sin((11pi)/6)-sin((17pi)/8))+i(sin(11π6)sin(17π8))

cos((11pi)/6)-cos((17pi)/8)=-2sin((95pi)/48)sin((-7pi)/48)cos(11π6)cos(17π8)=2sin(95π48)sin(7π48)
sin((11pi)/6)-sin((17pi)/8)=2cos((95pi)/48)sin((-7pi)/48)sin(11π6)sin(17π8)=2cos(95π48)sin(7π48)

e^((11pi)/6i)-e^((17pi)/8i)=-2sin((95pi)/48)sin((-7pi)/48)+i(2cos((95pi)/48)sin((-7pi)/48))e11π6ie17π8i=2sin(95π48)sin(7π48)+i(2cos(95π48)sin(7π48))

(95pi)/48=6.21895π48=6.218
(7pi)/48=0.4587π48=0.458

cos((95pi)/48)=0.998cos(95π48)=0.998
sin((95pi)/48)=-0.0654sin(95π48)=0.0654
cos((-7pi)/48)=0.897cos(7π48)=0.897
sin((-7pi)/48)=-0.442sin(7π48)=0.442

-2(-0.0654)xx(-0.442)+i(2(0.998)xx(-0.442)2(0.0654)×(0.442)+i(2(0.998)×(0.442)

2xx0.0654xx0.442-2xx0.998xx0.442i2×0.0654×0.4422×0.998×0.442i

e^((11pi)/6i)-e^((17pi)/8i)=0.058-0.882ie11π6ie17π8i=0.0580.882i

r=sqrt(0.058^2+(-0.882)^2=0.884r=0.0582+(0.882)2=0.884

theta=tan^-1(-0.882)/(0.058)=-1.505θ=tan1(0.882)0.058=1.505

0.058-0.882i=0.884(cos(-1.505)+isin(-1.505))0.0580.882i=0.884(cos(1.505)+isin(1.505))

cos(-1.505)+isin(-1.505)=e^((-1.505)icos(1.505)+isin(1.505)=e(1.505)i
e^((11pi)/6i)-e^((17pi)/8i)=0.884e^(-1.505i)e11π6ie17π8i=0.884e1.505i